ABCB1 Amplicon Contains Cyclic AMP Response Element-Driven TRIP6 Gene in Taxane-Resistant MCF-7 Breast Cancer Sublines - Daniel, Petr; Balušíková, Kamila; Václavíková, Radka; Šeborová, Karolína; Ransdorfová, Šárka; Valeriánová, Marie; Wei, Longfei; Jelínek, Michael; Tlapáková, Tereza; Fleischer, Thomas; Kristensen, Vessela N; Souček, Pavel; et al. (Genes, 2023)
A limited number of studies are devoted to regulating TRIP6 expression in cancer. Hence, we aimed to unveil the regulation of TRIP6 expression in MCF-7 breast cancer cells (with high TRIP6 expression) and taxane-resistant MCF-7 sublines (manifesting even higher TRIP6 expression). We found that TRIP6 transcription is regulated primarily by the cyclic AMP response element (CRE) in hypomethylated proximal promoters in both taxane-sensitive and taxane-resistant MCF-7 cells. Furthermore, in taxane-resistant MCF-7 sublines, TRIP6 co-amplification with the neighboring ABCB1 gene, as witnessed by fluorescence in situ hybridization (FISH), led to TRIP6 overexpression. Ultimately, we found high TRIP6 mRNA levels in progesterone receptor-positive breast cancer and samples resected from premenopausal women.
Keywords: Drug Resistance, Neoplasm; Response Elements; AMP cyklický; Female; transkripční faktory; Adaptor Proteins, Signal Transducing; responzivní elementy; ženské pohlaví; Neoplasms; adaptorové proteiny signální transdukční; MFC-7 buňky; nádory; LIM Domain Proteins; lidé; ATP Binding Cassette Transporter, Subfamily B; MCF-7 Cells; chemorezistence; Transcription Factors; Taxoids; P-glykoproteiny; Cyclic AMP; proteiny s doménou LIM; hybridizace in situ fluorescenční; In Situ Hybridization, Fluorescence; taxoidy; Humans